Hit and (they will) run: The impact of terrorism on migration - Dreher, Axel; Krieger, Tim; Meierrieks, Daniel (Economics letters, 2011)
We analyze the influence of terrorism on migration for 152 countries during 1976-2000. We find robust evidence that terrorism is among the ‘push factors’ of skilled migration, whereas it is not robustly associated with average migration.
Gesehen am 29.03.2022
Keywords: 1976-2000